Worldwide burden and epidemiological trends of tracheal, bronchus, and lung cancer: A population-based study - Bolun Zhou; Ruochuan Zang; Moyan Zhang; Peng Song; Lei Liu; Fenglong Bie; Yue Peng; Guangyu Bai; Shugeng Gao (EBioMedicine, 2022)
Summary: Background: We comprehensively analyzed the global burdens and trends in incidence and mortality of tracheal, bronchus, and lung (TBL) cancer among subgroups of distinctive ages and genders. Methods: We retrieved incidence and mortality rates of lung cancer in 2020 from the GLOBOCAN database among 185 countries. The incidence and mortality age-standardized rates (ASRs) were mostly obtained from Cancer Incidence in Five Continents and World Health Organization mortality database, respectively. The joinpoint regression analysis has been conducted to evaluate the average annual percentage change of incidence and mortality in recent years. Findings: Trends in the incidence and mortality were decreasing among men in most countries, whereas the trends were increasing among women in some regions. As for mortality, most countries had a decreasing trend in mortality among males, but increasing trends were observed in more than half of countries among females. Furthermore, the majority of countries showed a significant decrease in incidence among males (AAPCs, -0·34 to -6·53), whereas most countries had a significant increase among females (AAPCs, 9·39 to 0·6), especially in European countries. In addition, a more drastic decrease was identified in the trends of the incidence among young people. 33 countries had a drastic decrease among males, especially in countries in Europe (AAPCs, -0·93 to -11·71). And 15 countries showed a significant decrease in incidence among young women (AAPCs, -0·94 to -9·35). Interpretation: Decreasing incidence and mortality trends were identified in TBL cancer, particularly among all-age men and women younger than 50 years old. But some other groups of individuals showed an opposite trend, such as women in European countries. More preventive interventions are required for the specific populations. Funding: A full list of funding bodies that contributed to this study can be found in the Acknowledgements section.